PELATIHAN INTERNET SEHAT DAN AMAN UNTUK PELAJAR PADA SMA SWASTA NURUL HASANAH: PELATIHAN INTERNET SEHAT DAN AMAN UNTUK PELAJAR PADA SMA SWASTA NURUL HASANAH - saragih, nidia (Publikasi Pengabdian Masyarakat, 2023)
Technology is becoming increasingly inseparable from daily human life, including accessing information related to learning in school. Students are often asked to actively participate in learning by completing assignments using the internet. Unfortunately, the development of the internet also brings negative impacts. Various criminal dangers are also growing through the internet media. This training aims to provide an understanding to students of SMA Nurul Hasanah about the dangers and negative effects of the internet, as well as how to use the internet in a healthy and appropriate manner.